Total Astragalus saponins can reverse type 2 diabetes mellitus-related intestinal dysbiosis and hepatic insulin resistance in vivo - Ma, Leilei; La, Xiaojin; Zhang, Biwei; Xu, Wenxuan; Tian, Chunyu; Fu, Qianru; Wang, Meng; Wu, Chenxi; Chen, Zhen; Chang, Hong; Li, Ji-an (Frontiers in Endocrinology, 2023)
Objective: Intestinal flora homeostasis in rats with type 2 diabetes mellitus (T2DM) was evaluated to explore the effects of total Astragalus saponins (TAS) on hepatic insulin resistance (IR). Methods: Six-week-old male Sprague-Dawley rats were fed high-fat and high-sugar feed for 4 weeks and intraperitoneally injected with streptozotocin to induce T2DM, and they were then randomly divided into control, model, metformin, and TAS groups. Stool, serum, colon, and liver samples were collected after 8 weeks of drug administration for relevant analyses. Results: TAS reduced fasting blood glucose, 2-hour postprandial blood glucose, area under the curve of oral glucose tolerance test, glycated serum protein, homeostasis model assessment of insulin resistance, total cholesterol, triglyceride, and low-density lipoprotein cholesterol levels in T2DM rats but increased insulin, Cpeptide, and high-density lipoprotein cholesterol levels. Moreover, TAS improved the morphology and structure of liver and colon tissues and improved the composition of the intestinal microbiome and bacterial community structure at different taxonomic levels. In addition, TAS increased the protein expression of hepatic IRS-1, PI3K, PDK1, and p-AKT and decreased the protein expression This is a provisional file, not the final typeset article of p-GSK-3β. Meanwhile, TAS increased the mRNA expression of liver PDK1, PI3K, and GS and decreased the mRNA expression of GSK-3β. Conclusion: TAS can ameliorate T2DM-related abnormal glucose and blood lipid metabolism, intestinal dysbiosis, and IR.